Ołtarz jako okno i lustro w konceptach ks. prof. Sebastiana Piskorskiego - Kurzej, Michał (TECHNE. Seria Nowa, 2018)
The metaphor of the altar as a window and a mirror is particularly suitable for a series of reredoses designed by Rev. Prof. Sebastian Piskorski, a professor of law at the JagiellonianUniversity, and a popular poet and preacher, who became a central figure of the artistic life, participating as a conceptor and administrator in the process of creating the most interesting complex works of holy art. And the reredoses of these works play a crucial role there, since they become a key which enables us to read the iconographic programme. Besides its common decorative function of the presentation of a supernatural reality, they also work as a mirror. At certain times, they take the sunlight that generates a short-lived effect within the reredos, opening a new meaningful layer for the audience. The very first work by Piskorski is the pilgrimaging establishment in Grodzisknear Skała, conducted between 1677 and 1691. It commemorates Blessed Salomea, who is said to have lived and eventually died there on 17 November 1268.Its chapel was designed in such a manner that,on that day,sunshine flooded her altar. In 1692,Piskorski was offered an opportunity to applysignificantly more magnificent artistic solutions, when the university charged him with the task of managing the construction works of the new collegiate of St. Anne. Presumably, he participated in a debate on the location and the design of the church in order to influence the positioning and arrangement of its main reredoses. Due to their specific deployment, sunlight could be used to connect the altars in the presbytery and both wings of the transept with the stages of the sun year. A significant element of the interior is the altar with relics of the university’s patron saint–Saint John Cantius. The key to comprehending its form is the cult which was built up around him, propagated by the legend according to which he obtained a supernatural illumination from Jesus Christ himself. In the mausole um, this illumination was depicted by the Lamb and a putto with the following inscription: ‘Et lucernaeiusest’, which points to the relics carried by personifications of the four faculties. The pillars that surround the grave are references to the white-stone supports, which – as tradition has it – originate from Salomon’s Holy Temple. On the supports, there stand the statues of Cantius’ blessed namesakes, who – just like him – were preachers and theologists. One of them, John the Baptist, points to the Lamb’s image, which, at the same time, is his attribute, reminding the onlookers that Cantiusbore his first name to honour him and was born on his feast day,which falls on the summer solstice. In the afternoon around that date, sunlight floods this composition, highlighting its meaning and indicating that Providence destined Cantiusfor sanctity. The light is reflected off the statue of the Lamb and its aureole, like in a mirror, and then it floods onto the worshippers who are kneeling in front of the altar.This can be interpreted as the act of transferring the illumination once granted to the saint himself. The design of two out of the three most important altars within the collegiate also involves the sunlight-reflecting effect. Opposite Cantius’ grave, there is a relief portraying the triumph of the Cross, adored by Saint John the Evangelist and the Mother of God who is supporting the dead body of Christ. In the mornings on the days around the equinox, sunlight floods this part of the composition, commemorating the date of Jesus’s death. The painting in the high altar is illuminated at the turn of December and January, when – in the evenings – aray of sunlight creates a natural aureole above the heads of the depicted figures. The most important of these is the Baby Jesus, whose birth was commonly associated with the winter solstice and the eve of this celebration is also the anniversary of Cantius’ death. The use of natural lighting within the interior of the church is associated with the works by Bernini, who introduced the light into the composition from a hidden source, i.e. in a fashion which,to a great extent,was independent of the season or the time of day. Piskorski, on the other hand, used direct sunlight, which, just like a spotlight, picks out a specific element of the interior for a short period of time, from several to a dozen or so days in the year.